2019
DOI: 10.11604/pamj.supp.2019.32.1.13287
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of intimate partner violence, before and during pregnancy among attendees of maternal and child health services, Enugu, Nigeria: Mixed method approach, January 2015

Abstract: Introduction Intimate Partner Violence (IPV) is an under-reported public health problem. This study determined the prevalence of IPV and types of IPV, complications and factors associated with IPV among women accessing health services. Methods we conducted a cross-sectional survey of 702 women accessing maternal and child health services in Enugu State, Nigeria using multi-stage sampling technique. Quantitative data was collected using semi-structured questionnaire, qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 9 publications
2
14
1
Order By: Relevance
“…The study also supports that younger age and poor financial status were associated with IPV during pregnancy as observed by Doi et al (2019). Another study shows that poverty, lack of education and food security lead to IPV during and after pregnancy (29,30). Appropriate interventions can minimize and control the IPV as various experiments became successful in many countries (31).…”
Section: Main Findingssupporting
confidence: 65%
“…The study also supports that younger age and poor financial status were associated with IPV during pregnancy as observed by Doi et al (2019). Another study shows that poverty, lack of education and food security lead to IPV during and after pregnancy (29,30). Appropriate interventions can minimize and control the IPV as various experiments became successful in many countries (31).…”
Section: Main Findingssupporting
confidence: 65%
“…However, information about IPV prevalence is not consistent. Whereas some studies indicate higher prevalence of IPV during pregnancy than before [ 11 ] or after [ 12 , 13 ] the pregnancy, other studies report a smaller prevalence [ 14 , 15 ]. Furthermore, the prevalence of IPV during pregnancy is reported to vary depending on the definition used [ 1 ], the screening strategy [ 16 , 17 ], and the development status of the population studied [ 10 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research also supports that younger age and poor financial status were associated with IPV during pregnancy as observed by Doi et al (2019). Another study showed that poverty, lack of education and food security is associated with IPV during and after pregnancy (30,31). Appropriate interventions have been shown to help minimize and control IPV as various experiments demonstrated at in several countries (32).…”
Section: Discussionmentioning
confidence: 67%